The where and when of T cell regulation in transplantation - Issa, F; Robb, R; Wood, K (2013)
Multiple cell types contribute to the peripheral regulation of T cell alloresponses in haematopoieitc cell transplantation (HCT) and solid organ transplantation (SOT). Of these, regulatory T cells (Tregs) are the principal players and have shown the greatest success in the therapeutic control of detrimental immune responses. Investigations into the induction, location, and mechanism of suppression utilised by Tregs to control alloreactive responses are ongoing. The activation and homing characteristics of Tregs are important to their regulatory capabilities, with activation and homing occurring in the same time and space as conventional T cells. This review discusses these characteristics and recent advances in the field as we move closer to the ultimate goal of utilising Tregs as treatment for allograft rejection and graft-versus-host disease (GvHD). © 2012 Elsevier Ltd.